Recombinant Pyrin Domain Protein Attenuates Airway Inflammation and Alleviates Epithelial-Mesenchymal Transition by Inhibiting Crosstalk Between TGFβ1 and Notch1 Signaling in Chronic Asthmatic Mice - Wang, Zhiguang; Li, Liangchang; Wang, Chongyang; Piao, Yihua; Jiang, Jingzhi; Li, Li; Yan, Guanghai; Piao, Hongmei (Frontiers in Physiology, 2020)
This article aims to investigate the effects of recombinant pyrin domain (RPYD) on airway inflammation and remodeling in mice with chronic asthma. The chronic asthma BALB / c mouse model was first sensitized by ovalbumin (OVA) and then challenged by OVA nebulization. RPYD or dexamethasone was given before OVA challenge. Our results showed that RPYD significantly inhibited the increase of total cell number, eosinophils, neutrophils and lymphocytes in bronchoalveolar lavage fluid (BALF) induced by OVA, and reduced the infiltration of inflammatory cells, the proliferation of goblet cells and collagen deposition. In addition, RPYD inhibited the mRNA and protein levels of α-smooth muscle actin (α-SMA), transforming growth factor (TGF)-β1, Jagged1, Notch1, Hes1 and Smad3, as well as Smad3 phosphorylation. TGFβ1 down-regulated the level of E-cadherin and promoted the expression of α-SMA, thus inducing epithelial-mesenchymal transition (EMT) in bronchial epithelial cells. We found that RPYD reduced EMT by inhibiting TGFβ1 / smad3 and Jagged1 / Notch1 signaling pathways. Further overexpression of NICD showed that under the stimulation of TGFβ1, NICD enhanced the phosphorylated Smad3 and nuclear Smad3, accompanied by the increased expression of Notch1 target gene Hes1. In contrast, after treatment with smad3 siRNA, the expression of Hes1 was down regulated as the decrease of Smad3, which indicates that there is crosstalk between smad3 and NICD on Hes1 expression. In conclusion, RPYD reduces airway inflammation, improves airway remodeling and reduces EMT in chronic asthmatic mice by inhibiting the crosstalk between TGFβ1/smad3 and Jagged1/Notch1 signaling pathways.